2001
DOI: 10.1016/s0016-7061(00)00110-5
|View full text |Cite
|
Sign up to set email alerts
|

Phosphate retention and extractability in soils of the humid zone in West Africa

Abstract: Phosphate adsorption and desorption studies provide insight for developing P management strategies. Very few studies have concentrated on P desorption which provides information on the reversibility of adsorbed P. Phosphate adsorption and desorption studies were carried out on seven rice-growing soils from three countries in West Africa, with the objective of relating these Ž. processes to P management strategies for the soils. The standard P requirement SPR of soils, defined as the amount of P to be added to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
12
0
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 18 publications
5
12
0
1
Order By: Relevance
“…Similar results for phosphate release were observed by Dev et al (1990) and Abekoe and Sahrawat (2001). Abekoe and Sahrawat (2001) observed that there was a sharp initial increase in phosphate release in the first 2 h followed by a continuous slight release to 16 h.…”
Section: Discussionsupporting
confidence: 88%
“…Similar results for phosphate release were observed by Dev et al (1990) and Abekoe and Sahrawat (2001). Abekoe and Sahrawat (2001) observed that there was a sharp initial increase in phosphate release in the first 2 h followed by a continuous slight release to 16 h.…”
Section: Discussionsupporting
confidence: 88%
“…In our study, the P concentration remained < 0.20 and 0.5 mg L -1 in the control treatments, while in the sludge-treated columns the amount of P leached was higher. Similar results for P release were observed by Dev et al (1990) and Abekoe and Sahrawat (2001). Abekoe and Sahrawat (2001) observed that there was a sharp initial increase in P release in the first 2 h followed by a continuous slow release up to 16 h.…”
Section: Leaching Of Phosphorussupporting
confidence: 89%
“…Similar results for P release were observed by Dev et al (1990) and Abekoe and Sahrawat (2001). Abekoe and Sahrawat (2001) observed that there was a sharp initial increase in P release in the first 2 h followed by a continued slow release up to 16 h.…”
Section: Soilssupporting
confidence: 89%